Ventral Striatal Activation During Reward Anticipation of Different Reward Probabilities in Adolescents and Adults - Bretzke, Maria; Wahl, Hannes; Plichta, Michael M.; Wolff, Nicole; Roessner, Veit; Vetter, Nora C.; Buse, Judith (Frontiers in Human Neuroscience, 2021)
Adolescence has been linked to an enhanced tolerance of uncertainty and risky behavior and is possibly connected to an increased response towards rewards. However, previous research has produced inconsistent findings. To investigate whether these findings are due to different reward probabilities used in the experimental design, we extended a monetary incentive delay (MID) task by including three different reward probabilities. Using functional magnetic resonance imaging, 25 healthy adolescents and 22 adults were studied during anticipation of rewards in the VS. Differently colored cue stimuli indicated either a monetary or control trial and symbolized different reward probabilities, to which the participants were blinded. Results demonstrated faster reaction times for lower reward probabilities (33 %) in both age groups. Adolescents were slower through all conditions and had less activation on a neural level. Imaging results showed a three-way interaction between age group x condition x reward probability with differences in percent signal change between adolescents and adults for the high reward probability (66%, 88 %) while adolescents demonstrated differences for the lowest (33 %). Therefore, previous inconsistent findings could be due to different reward probabilities, which makes the examining these crucial for a better understanding of adolescent and adult behavior.